2018
DOI: 10.26644/em.2018.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Daily Exercise Compared to Exercise on Alternating Days on Post-Exercise Blood Pressure Reduction in Men with Elevated Blood Pressure

Abstract: History: Objectives: Acute exercise can result in post-exercise hypotension (PEH) lasting up to 24-h. Whether exercise performed on consecutive days would lead to an accumulating PEH effect has yet to be determined. The purpose of this study was to compare daily exercise (DE) to exercise performed on alternating days (AE) and control (CON) on PEH. Methods: Sedentary men 18-30 yr with elevated blood pressure (BP) participated in this three-arm randomized cross-over trial. The primary comparison was PEH between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, very few said that they understood that walking and running were the only forms of exercises. This was corroborated by Somani, 31 Comelissen et al, 40 and Zeigler et al 41 It is common knowledge that walking and jogging in the streets and walkways are good types of exercises; however, security threats are deterrents for many people in South Africa to undertake them. Lastly, the participants were assessed about the level of stress in their lives as it has been reported that stress may negatively impact BP control.…”
Section: Exercise Frequency and Typesmentioning
confidence: 73%
“…Furthermore, very few said that they understood that walking and running were the only forms of exercises. This was corroborated by Somani, 31 Comelissen et al, 40 and Zeigler et al 41 It is common knowledge that walking and jogging in the streets and walkways are good types of exercises; however, security threats are deterrents for many people in South Africa to undertake them. Lastly, the participants were assessed about the level of stress in their lives as it has been reported that stress may negatively impact BP control.…”
Section: Exercise Frequency and Typesmentioning
confidence: 73%